Scanxiety: a scoping review about scan-associated anxiety. Issue 5 (26th May 2021) - Bui, Kim Tam; Liang, Roger; Kiely, Belinda E; Brown, Chris; Dhillon, Haryana M; Blinman, Prunella
Abstract : Objectives: To identify available literature on prevalence, severity and contributing factors of scan-associated anxiety ('scanxiety') and interventions to reduce it. Design: Systematic scoping review. Data sources: Ovid MEDLINE, Ovid EMBASE, Ovid PsycINFO, Ovid Cochrane Central Register of Controlled Trials, Scopus, EBSCO CINAHL and PubMed up to July 2020. Study selection: Eligible studies recruited people having cancer-related non-invasive scans (including screening) and contained a quantitative assessment of scanxiety. Data extraction: Demographics and scanxiety outcomes were recorded, and data were summarised by descriptive statistics. Results: Of 26 693 citations, 57 studies were included across a range of scan types (mammogram: 26/57, 46%; positron-emission tomography: 14/57, 25%; CT: 14/57, 25%) and designs (observation: 47/57, 82%; intervention: 10/57, 18%). Eighty-one measurement tools were used to quantify prevalence and/or severity of scanxiety, including purpose-designed Likert scales (17/81, 21%); the State Trait Anxiety Inventory (14/81, 17%) and the Hospital Anxiety and Depression Scale (9/81, 11%). Scanxiety prevalence ranged from 0% to 64% (above prespecified thresholds) or from 13% to 83% ('any' anxiety, if no threshold). Mean severity scores appeared low in almost all measures that quantitatively measured scanxiety (54/62, 87%), regardless of whether anxiety thresholds were prespecified. Moderate to severe scanxiety occurred in 4%–28% of people in studies using descriptive measures. Nine of 20 studies assessing scanxiety prescan and postscan reported significant postscan reduction in scanxiety. Lower education, smoking, higher levels of pain, higher perceived risk of cancer and diagnostic scans (vs screening scans) consistently correlated with higher scanxiety severity but not age, gender, ethnicity or marital status. Interventions included relaxation, distraction, education and psychological support. Six of 10 interventions showed a reduction in scanxiety. Conclusions: Prevalence and severity of scanxiety varied widely likely due to heterogeneous methods of measurement. A uniform approach to evaluating scanxiety will improve understanding of the phenomenon and help guide interventions.